Chemical control of the common bacterial blight of bean and its effect in the tansmission of Xanthomonas campestris pv. phaseoli (Smith) Dye by seeds. - Maringoni, Antonio Carlos (Pesquisa Agropecuaria Brasileira, 2014)
Two experiments were carried out during the rainy season of 1987, in Paraná state, Brazil, with an objective of evaluating the chemical control of the common bacterial blight of bean (Phaseolus vulgaris L.) in the Rio Negro cultivar. The chemicals streptomycin plus oxitetracidlin, copper oxychloride plus zineb, copper oxychloride plus mancozeb and copper oxychloride were sprayed three times under field conditions. A low efficiency in the control of that bacterial disease was observed by the occurrence of a high severity of this disease on leaves; high incidence of pods with the disease and a high level of X. campestris pv. phaseoli on the seeds were also observed. There were yield increases due to chemical treatmentments with copper oxychloride plus zineb and copper oxychloride plus mancozeb